Competition Advocacy Challenges for Developing Countries - Clark, John (OECD Publishing, 2005)
Competition advocacy is especially critical for developing countries as their economic policies are undergoing fundamental market driven changes. Prerequisites for effective competition advocacy by a competition agency include a significant degree of independence from political influence, sufficient resource to support both its enforcement and advocacy functions, and credibility as an effective and impartial advocate for competition. Opportunities for competition advocacy are numerous: privatization; legislation, government policy and regulatory reform. The Second Latin American Competition Forum, jointly sponsored by the OECD and the Interamerican Development Bank (Washington 14-15 June 2004) discussed the...